The role of journalism in shaping news and creating the image of COVID-19 in the mass media based on selected examples - Stępień-Kowalik, Klaudia (Zjawiska propagandy i manipulacji w prasie, telewizji, radiu i Internecie, 2022)
The aim of this article is to describe the importance and the condition of the contemporary journalism by referring to dynamic changes, which occurred during the pandemic. Radio, TV and Internet formats were analyzed especially. The primary question refers to the quality of social media materials prepared by journalists. Considerations were made by using the method of analysis, the method of analogy and the analysis of source texts.